2012
DOI: 10.1161/circep.111.966754
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter Defibrillator Therapy in Adults With Congenital Heart Disease

Abstract: Adults with CHD and ICDs receive high rates of appropriate and effective shocks. Patients with secondary prevention indication, coronary artery disease, and symptomatic NSVT are at highest risk of receiving appropriate ICD shocks. ICD implantation is accompanied by considerable morbidity, including inappropriate shocks and procedure- related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 26 publications
2
51
0
6
Order By: Relevance
“…W sumie w ostatnich 2 dekadach leczenie za pomocą ICD u pacjentów z wrodzonymi wadami serca zmieniło charakter z prewencji wtórnej na pierwotną [490,491]. W retrospektywnych badaniach kohortowych wykazano, że oprócz VA również upośledzona czynność komory, lewej lub prawej, stała się niezmiennym czynnikiem ryzyka SCD u pacjentów z różnymi typami wrodzonych wad serca [493-495, 497, 498].…”
Section: Nagły Zgon Sercowy I Komoroweunclassified
“…W sumie w ostatnich 2 dekadach leczenie za pomocą ICD u pacjentów z wrodzonymi wadami serca zmieniło charakter z prewencji wtórnej na pierwotną [490,491]. W retrospektywnych badaniach kohortowych wykazano, że oprócz VA również upośledzona czynność komory, lewej lub prawej, stała się niezmiennym czynnikiem ryzyka SCD u pacjentów z różnymi typami wrodzonych wad serca [493-495, 497, 498].…”
Section: Nagły Zgon Sercowy I Komoroweunclassified
“…Koyak et al noted that ATP was effective in 5 of 26 repaired TOF patients. 3 In contrast, Witte et al found that ATP was highly effective in 4 of 4 repaired TOF patients. 5 In the present study, ATP was highly effective in 9 of 11 patients in whom ATP was attempted.…”
Section: Overall Survivalmentioning
confidence: 95%
“…Multi-central retrospective study by Koyak et al described non-sustained VTs as significant predictor for appropriate ICD shocks (HR 9.1, 95% CI 2.8-29.2, p < 0.001) [71]. Indication for secondary prevention was also associated with higher risk of appropriate shocks (HR 3.6, 95% CI 1.3-9.5, p = 0.009).…”
Section: Implantable Cardioverter-defibrillatormentioning
confidence: 99%
“…Importantly, patients with rTOF experience higher incidence of receiving inappropriate ICD shocks compared to patients with other CHDs (HR 3.6, 95% CI 1.0-12.4, p < 0.048) [71]. This often has negative impact on the mental state of these patients [69].…”
Section: Implantable Cardioverter-defibrillatormentioning
confidence: 99%